Assessment of the genotypes of jersey cows by the molecular markers of the kappa-casein gene - Glotova Galina; Pozolotina Valentina (BIO Web of Conferences, 2023)
The article is devoted to an urgent issue in the era of import substitution – the search for markers that can increase milk productivity. As the obtained research results have shown, genotyping using allelic variants of the kappa-casein gene will make it possible to make and generalize the selection and picking of the desired animal genotypes for practical breeding in order to increase protein content.